ALU transposition induces familial hypertrophic cardiomyopathy. Issue 1 (30th September 2019) - Nfonsam, Landry; Huang, Lijia; Carson, Nancy; McGowan‐Jordan, Jean; Beaulieu Bergeron, Melanie; Goobie, Sharan; Conacher, Susan; McCarty, David; Benson, Lee; Hewson, Stacy; Zahavich, Laura; Sinclair‐Bourque, Elizabeth; et al.
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is characterized by left ventricular hypertrophy (LVH) in the absence of predisposing cardiovascular conditions. Pathogenic variants in at least 16 cardiac sarcomeric genes have been implicated in HCM, most of which act in a dominant‐negative fashion. However loss‐of‐function (haploinsufficiency) is the most common disease mechanism for pathogenic variants in MYBPC3, suggesting that MYBPC3 complete deletion may play a role in HCM pathogenesis. Here, we investigate MYBPC3 complete deletion as a disease mechanism in HCM by analyzing two unrelated patients with confirmed diagnosis of HCM that tested negative by Sanger sequencing analysis. Methods: MYBPC3 complete deletion was investigated by Multiplex ligation‐dependent probe amplification (MLPA) and microarray analyses. The mechanism of deletion was investigated by interrogating the SINEBase database. Results: Patient‐1 was diagnosed with nonobstructive HCM in his mid‐40s while undergoing assessment for palpitations, and patient‐2 with obstructive HCM in his late‐20s while undergoing systolic heart murmur assessment for an unrelated illness. MLPA testing revealed a heterozygous deletion of all MYBPC3 exons in both patients. Subsequent microarray testing confirmed these deletions which extended beyond the 5′ and 3′ ends of MYBPC3 . Genomic assessment suggested that these deletions resulted from Alu/Alu ‐homologous recombination. Conclusion: Our results demonstrate that haploinsufficiency resulting from MYBPC3 complete deletion, potentially mediated by Alu recombination, is an important disease mechanism in cardiomyopathy and emphasizes the importance of copy number variation analysis in patients clinically suspected of HCM. Abstract : We report on the complete deletion of MYBPC3, potentially mediated through Alu recombination, in two patients with confirmed diagnosis of hypertrophic cardiomyopathy (HCM). Our result demonstrates for the first time that MYBPC3 complete deletion is an important disease mechanism in cardiomyopathy and emphasizes the importance of copy number variation analysis in patients clinically suspected of HCM.